The Social Construction of Intensive Care Nursing, 1960-2002: Canadian Historical Perspectives - Vanderspank, Brandi (Université d'Ottawa / University of Ottawa, 2014)
Intensive care units (ICUs) emerged across Canada during the early 1960s, significantly contributing to the image of Western hospitals as places of scientific advancement that predominated over much of the twentieth century. ICUs rapidly became both a resource intensive and expensive type of care as the number and size of units increased to accommodate diverse patient populations and treatment options. Nurses enabled the formation and growth of ICUs through their constant presence and skilled care. There has been limited research, however, regarding the historical development of Canadian ICUs, the relationships between nurses and other personnel in such units, how they developed an identity as ICU nurses, or how ICU nursing became a specialty practice. Situated within the broader histories of hospitals, healthcare, and nursing, this study uses a social history approach to examine nurses’ experiences within Canadian ICUs between 1960 and 2002. Berger and Luckmann’s Social Construction of Reality provided a lens for analysis and interpretation of oral histories, photographs, professional literature of the time period under study, and both archival and organizational records. This thesis argues that ICU nurses’ relationships with one another, in the context of a technologically complex environment, socially constructed their knowledge and skill acquisition, their socialization as ICU nurses, and the development of a specialized body of knowledge that ultimately led to formal recognition of ICU nursing as a specialty in Canada.
Keywords: Nursing; Critical Care; History of Critical Care; History of Intensive Care Units; History of Nursing; Social History